TOXICITY TEST DIETHYL ETHER EKSTRACT OXALIS CORNICULATA L. HERB ON BRINE SHRIMP LETHALITY TEST METHOD - Herwin, Herwin; Kosman, Rachmat; Baits, Muzakkir (Fakultas Farmasi UMI, 2014)
Recearch toxicity effect of standar dietil eter ekstract Oxalis corniculata L. herb at Artemia salina Leach with purpose to determine toxicity potencial and LC50 value Oxalis corniculata L. herb on brine shrimp lethality test method. The result of this research shows that diethyl ether ekstract Oxalis corniculata L. herb at concentration 100, 50, 5, 1, 0.5, 0.1, 0.05, 0.01 µg/ml and controler is diethyl ether. Presentation data of Artemia salina Leach larvae was analyzed with probit analysis to count LC50. Ekstract is toxic if LC50 value < 1000 µg/ml. So obtained that diethyl ether ekstrak Oxalis corniculata L. herb is toxit to Artemia salina Leach larvae with LC50 4,17± 2,59 µg/ml. Key words : Oxalis corniculata L, Toxicity, Brine Shrimp Lethality Test.